Correlation Between Body Mass Index and Calf Circumference in Assessing the Nutritional Status of the Elderly - Cecilia Antolin; Meilani Kumala (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
An increase in fat mass and a decrease in muscle mass are common physiological changes in the elderly. The loss of muscle mass increases the risk of sarcopenia, which negatively affects physical function. Therefore, accurate assessment of nutritional status in the elderly is crucial. Body Mass Index (BMI) is commonly used but cannot distinguish between fat mass and muscle mass. Calf circumference serves as a simple and practical anthropometric alternative to estimate muscle mass. This study aims to determine the correlation between BMI and calf circumference in assessing the nutritional status of elderly individuals aged ≥46 years. This research employed an analytical observational design with a cross-sectional approach, conducted at three locations during the 2024–2025 period. A total of 75 respondents who met the inclusion and exclusion criteria were included. Data were obtained through measurements of height, weight, and calf circumference. The analysis showed a significant correlation between BMI and calf circumference (p < 0.05). Conclusion: Calf circumference can serve as an important additional indicator in assessing the nutritional status of the elderly. The combination of BMI and calf circumference provides more comprehensive information for evaluating the nutritional status in the elderly population.